Correlation between metabolic dysfunction-associated steatotic liver disease and subclinical coronary atherosclerosis in eastern China - Guanghui Ma; Guohou Xu; Haixia Huang (Diabetology & Metabolic Syndrome)
Abstract Background Metabolic dysfunction-associated steatotic liver disease (MASLD) is characterized by the presence of at least one cardiovascular disease (CVD) risk factor, underscoring its potential to elevate CVD risk in affected individuals. However, evidence linking MASLD to subclinical coronary atherosclerosis remains scarce, and further investigations are necessary to elucidate the independent role of varying MASLD severities as a CVD risk factor. Methods This study analyzed 7,507 participants aged ≥ 40 who underwent comprehensive health evaluations at the Shanghai Health and Medical Center. Logistic regression analysis was utilized to explore the relationship between MASLD severity and the presence of coronary artery calcification (CAC). Correlation analysis was performed to assess the association between MASLD severity and CAC staging. Results After adjusting for established CVD risk factors, MASLD showed a significant association with CAC, which intensified with increasing MASLD severity. Among individuals with hypertension, MASLD was markedly correlated with CAC. In contrast, in non-hypertensive participants, only moderate and severe MASLD were significantly associated with CAC, while mild MASLD demonstrated no notable link, even after adjustment for CVD risk factors. Moreover, correlation analysis revealed a positive association between MASLD severity and CAC staging, indicating that higher MASLD severity aligned with more advanced CAC stages. Conclusion This study highlighted that MASLD severity was independently associated with subclinical atherosclerosis, irrespective of traditional CVD risk factors, in an urban eastern Chinese population without a prior history of coronary atherosclerosis. The strongest associations were observed in individuals with severe MASLD, emphasizing the importance of assessing MASLD severity in CVD risk stratification.